(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Empress Theodora portrayed in the famous mosaic of San Vitale in Ravenna has contributed to establish her position in the following visual imaginary and has been quoted in many works of art, to the extent of having been considered her only depiction realized in her epoch. But it is an official and idealized portrait, which gives us very few information about Theodora’s actual look, so that many other works of art, in the following centuries, have been considered as her portraits simply because there were no information about the persons they actually represented.